Review of human papillomavirus (HPV) burden and HPV vaccination for gay, bisexual, and other men who have sex with men and transgender women in the United States. Issue 1 (31st January 2022) - Meites, Elissa; Wilkin, Timothy J.; Markowitz, Lauri E.
ABSTRACT: Gay, bisexual, and other men who have sex with men (MSM) and transgender women, particularly those who are living with HIV, are disproportionately affected by human papillomavirus (HPV). For this narrative review of HPV health outcomes and vaccination for gay, bisexual, and other MSM and transgender women in the United States, we highlighted 71 publications regarding 1) burden of HPV infections and related diseases; 2) HPV vaccine efficacy; 3) HPV vaccination recommendations; 4) HPV vaccination coverage; 5) real-world vaccine effectiveness and health impacts; and 6) HPV vaccination acceptability. Vaccination is effective at reducing HPV infections among MSM; in the United States, routine HPV vaccination is recommended for all adolescents at age 11–12 years and for all persons through age 26 years. Efforts are ongoing to increase vaccination coverage and monitor health impacts of vaccination. Increasing vaccination coverage before sexual exposure to HPV is expected to reduce the burden of HPV-related disease.